Quantum transport in DNA modulated by a Schiff base ligand: The role of binding and electronic structure changes from DFT-NEGF-MD simulations - Karakurt, Tuncay; Cukurovali, Alaaddin; Mohammad, Hashem; Yilmaz, Ibrahim (Elsevier Science Inc, 2026)
DNA has emerged as a promising molecular system for nanoscale electronics owing to its self-assembly, programmability, and pi-orbital delocalization. Here, we investigate the quantum charge transport behavior of a canonical 12-base-pair B-DNA duplex (RCSB ID: 102d, 5 '-CGCAAATTTGCG-3 ') and its Schiff-base ligand-bound complexes. The ligand, 2-methoxy-4-((2-(4-(3-methyl-3-phenylcyclobutyl)thiazol-2-yl)hydrazono)methyl)phenol (C22H23N3O2S), was synthesized and structurally characterized via NMR and single-crystal X-ray diffraction. Quantum transport properties were computed using density functional theory combined with the nonequilibrium Green's function (DFT-NEGF) formalism including decoherence corrections. Transmission spectra Teff(E) and conductance G(E-F) were analyzed for bare and ligand-modified DNA systems. HOMO orbitals were found to localize strongly on the ligands, reducing conductance by similar to 67-76 % relative to 102d. Classical molecular dynamics and MM/GBSA binding-energy analyses were used to explore potential relationships between ligand binding strength, orbital localization, and transport suppression. Within the statistical uncertainty of the free-energy estimates, the calculations support a qualitative trend in which configurations with stronger enthalpic stabilization tend to exhibit enhanced HOMO localization and reduced conductance. However, the absence of a simple one-to-one correlation indicates that electronic transport is governed more by the specific binding mode and the resulting orbital redistribution than by the magnitude of binding affinity alone. These results therefore suggest a complex interplay between binding thermodynamics and quantum conductance, highlighting the dual role of ligand intercalation in stabilizing DNA while modulating its electronic delocalization.
Keywords: DNA charge transport; Schiff base ligand; DFT-NEGF; Molecular dynamics; HOMO-LUMO alignment; Energy-independent decoherence